KEANEKARAGAMAN JENIS BAMBU DI KAWASAN KEBUN RAYA SAMBAS KECAMATAN SUBAH KABUPATEN SAMBAS PROVINSI KALIMANTAN BARAT - Vinsensia, Miranda; Herawatiningsih, Ratna; Tavita, Gusti Eva (Universitas Tanjungpura, 2020)
Bamboo is one of the results of a non-timber forest that grows in the secondary forest and open forest, and can even be found in Sambas Botanical garden area. The purpose of this research is to determine the value of the diversity of bamboo in the area of Sambas Botanical Garden, Subah subdistrict, Sambas Regency, West Kalimantan. This research was conducted in Sambas Botanical Garden, Â starting from 09 July 2019 until 27 July 2019 then continued by analysis of data. The collection of bamboo data at the research site is conducted by the survey method and performed purposive sampling with a plot laying of research samples using a double tile, with the size of each tile example 10 m x 10 m. Results showed in the Sambas Botanical Garden 5 species of bamboo had been found consisting of 3 different genera namely Bambu Tali (Gigantochloa hasskarliana Kurz.), Bambu Lemang (Schizostachyum brachycladum Kurz.), Bambu Tamiang (Schizostachyum latifolium), Schizostachyum terminale Holtt. Bamboo, and Bambu Merambat (Dinochloa sp.). Important Values Index of Bambu Merambat, Bambu Tali, Bambu Lemang, Bambu Tamiang, and Bambu Schizostachyum terminale Holtt. are 77.3251%, 47.0843%; 31.6900%; 24.4437%; and 19.1943% respectively. Dominancy index of Bambu Merambat, Bambu Tali, Bambu Lemang, Bambu Tamiang, and Bambu Schizostachyum terminale Holtt. are 0.1647; 0.0680; 0.0254; 0.0076; and 0.0076 respectively. Index diversity species (H ') of Bambu Merambat, Bambu Tali, Bambu Lemang, Bambu Tamiang, and Bambu Schizostachyum terminale Holtt. are 0.1589; 0.1522; 0.1271; 0.0922; and 0.0922 respectively. All species of bamboo found in this research have a value of H ' Ë‚ 1 then all species of bamboo were categorized as low value of species diversity.Keywords: Bamboo, Diversity, Sambas Botanical Garden